Legitimating life : adoption in the age of globalization and biotechnology - Wichelen, Sonja van (Book collections on Project MUSE., 2019)
The phenomenon of transnational adoption is changing in the age of globalization and biotechnology. In Legitimating Life, Sonja van Wichelen boldly describes how contemporary justifications of cross-border adoption navigate between child welfare, humanitarianism, family making, capitalism, science, and health. Focusing on contemporary institutional practices of adoption in the United States and the Netherlands, she traces how professionals, bureaucrats, lawyers, politicians, social workers, and experts legitimate a practice that became progressively controversial. Throughout the past few decades transnational adoption transformed from a humanitarian response to a means of making family. In this new manifestation, life becomes necessarily economized. While push and pull factors, demand and supply dynamics, and competition between agencies set the stage for the globalization of adoption, international conventions, scientific knowledge, and the language of human rights universalized the phenomenon. Van Wichelen argues that such technoscientific legitimations of a globalizing practice are rearticulating colonial logics of race and civilization. Yet, she also lets us see beyond the biopolitical project and into alternative ways of making kin.